PERAN PEMERINTAH, LEMBAGA ADAT DAN MODAL SOSIAL DALAM PEMBERDAYAAN INDUSTRI KECIL DAN MENENGAH (STUDI PADA INDUSTRI KERAJINAN DI PROVINSI BALI) - Ni Nyoman Yuliarmi ; Prof. Agus Suman, SE., DEA., Ph.D, Prof. Dra. S. M. Kiptiyah, M.Sc, Prof. Ahmad Erani Yustika, SE, M.Sc., Ph.D (Disertasi Ilmu Ekonomi FEB-UB, 2011)
Promotor: S.M. Kiptiyah and Ahmad Erani Yustika. Government and related-institution has been done development program to improve SME self-efficacious. However, to there are many small industry, especially handicraft industry that can not compete globally. Bali Boom have large impact to Small and Medium Enterprise. It make production decrease, selling lower, and very difficult to sell their handicraft. Bali Boom make a disaster to Bali Economics that grow rapidly last ago. The aims of this research determine : 1) effect of the role of government that has been done by Disperindag and institutions-related to empowering SMEs, 2) the effect of social, cultural, economic and custom financial institutions roles on SMEs empowerment, 3) the effect of social capital on social, cultural, economic and custom financial institutions roles to empower SMEs, 4) the effect of social capital on government role to empower SME, 5) the effect of social capital on SME empowerment, 6) the effect the government role on social, cultural, economic and custom financial institutions roles to empower SMEs. The population in this research are all SMEs actor at districts/county in Bali Province. To determine the sample, it is used purposive sampling method, based on the largest business units from their respective districts. The number of sample units represented by this population in each district is selected by stratified random sampling method. The number of samples obtained at least 204 people. The accidental sampling method is used to determine craftsmen who will be interviewed. The officials and traditional leaders selected are those who competent in their respective fields. This research uses quantitative analysis approach